Comparative Epidemiology and Outcomes of Human Immunodeficiency virus (HIV), Non-HIV Non-transplant, and Solid Organ Transplant Associated Cryptococcosis: A Population-Based Study. (4th October 2017) - George, Ige A; Spec, Andrej; Powderly, William G; Santos, Carlos A Q
Abstract: In this population-based study in the contemporary era in the United States, the proportion of human immunodeficiency virus (HIV)–negative patients with cryptococcosis approaches that in HIV-infected patients. Cryptococcosis is associated with higher mortality rates in HIV-negative patients (including organ transplant recipients).